Isolation, Characterization and Application of Micro Satellite Markers in the Southeast Asian River Catfish (Baung) Mystus Nemurus (C&V) - Usmani, Sahar (2002)
In Malaysia 70% of the dietary protein comes from fish. The popularity of the river catfish Mystus nemurus throughout Malaysia and also Southeast Asia has made it an important aquaculture candidate. Among the vast choice of molecular markers available to carry out a population study including stock identification and improvement, microsatellites have proven to be the most efficient. The main objectives of this study were: (1) to develop efficient microsatellite isolation protocols for Mystus nemurus followed by a population study using the newly developed microsatellite markers and (2) to test two new techniques, direct amplification of length polymorphism (DALP) and random hybridising microsatellites (RAHM), as potential DNA fingerprinting markers for population studies.